The students’ aggressiveness in senior high school based on gender - Anna Ayu Herawati; Herman Nirwana; Syahniar Syahniar (International Conferences on Educational, Social Sciences and Technology)
Student has a different level of aggressiveness, this was influenced by various factors one of them is gender. Aims of this research is to examine differences the aggressiveness students based on gender. The method was ex post facto with a 2 groups design. Thepopulation is 566 and samples were 234 students. Sampling technique used stratified random sampling.The instrument usedAggressiveness Scale, with reliability scoreis 0,936. Data were analyzed by using the descriptive statistics and anova. The results of this research show that there is a significant difference of aggressiveness in terms of gender. The implication of this research can be used as students need assessment to make improvement a program of guidance and counseling.